A CASE REPORT OF DIABETIC KETOACIDOSIS IN A PREGNANT PATIENT NOT PREVIOUSLY KNOWN TO BE DIABETIC AND WITH NORMAL HbA1c LEVEL - AntoinetteYoung, Louisse Lynn; Paitao, Abulheir; Chang, Alan (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE Diabetic ketoacidosis (DKA) in the pregnant population has grave effects on the fetus and mother if left untreated. It is unusual for a non-diabetic pregnant woman to develop DKA during pregnancy. This is a case of a 32-year-old Filipino gravida 3 para 2, 29 weeks and 3/7 days pregnant, who presented with shortness of breath. Laboratory tests showed an elevated blood glucose level >600 mg/dL, high anion gap metabolic acidosis, and ketonuria, but with a normal HbA1c level. The patient was managed as newly diagnosed diabetes mellitus in severe diabetic ketoacidosis. She was started on fluid replacement, insulin therapy, and antibiotic treatment for urinary tract infections. However, due to fetal demise, she underwent induction of labor and subsequent delivery. DKA may occur in pregnant women not previously known to have diabetes and confers a high mortality risk if left undetected. Thus, a high index of suspicion is needed even if patients initially showed normal glucose tolerance or HbA1c levels.